1999
DOI: 10.1104/pp.120.4.1183
|View full text |Cite
|
Sign up to set email alerts
|

Does Free-Air Carbon Dioxide Enrichment Affect Photochemical Energy Use by Evergreen Trees in Different Seasons? A Chlorophyll Fluorescence Study of Mature Loblolly Pine1

Abstract: Previous studies of the effects of growth at elevated CO 2 on energy partitioning in the photosynthetic apparatus have produced conflicting results. The hypothesis was developed and tested that elevated CO 2 increases photochemical energy use when there is a high demand for assimilates and decreases usage when demand is low. Modulated chlorophyll a fluorescence and leaf gas exchange were measured on needles at the top of a mature, 12-m loblolly pine (Pinus taeda L.) forest. Trees were exposed to ambient CO 2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 38 publications
9
64
0
1
Order By: Relevance
“…It has been shown that ΦPSII (or ETR) measured in the light was linearly correlated to the quantum yield of oxygen or CO 2 uptake in C3 higher plants when photorespiration was avoided (Genty et al, 1989;Krall and Edwards, 1990;Cornic and Ghashghaie, 1991;Genty and Meyer, 1995;Hymus et al, 1999). This finding permitted the use of simple fluorescence measurements to estimate the CO 2 uptake and the productivity of plants.…”
Section: Fluorescence and Oxygen Evolution Measurements On Dark-adaptmentioning
confidence: 94%
“…It has been shown that ΦPSII (or ETR) measured in the light was linearly correlated to the quantum yield of oxygen or CO 2 uptake in C3 higher plants when photorespiration was avoided (Genty et al, 1989;Krall and Edwards, 1990;Cornic and Ghashghaie, 1991;Genty and Meyer, 1995;Hymus et al, 1999). This finding permitted the use of simple fluorescence measurements to estimate the CO 2 uptake and the productivity of plants.…”
Section: Fluorescence and Oxygen Evolution Measurements On Dark-adaptmentioning
confidence: 94%
“…In addition, J o will be competitively suppressed by increasing pCO 2 . Many studies have shown no effect of growth in elevated pCO 2 on sinks for J t , other than carbon metabolism (Epron et al, 1994;Habash et al, 1995; Bartak et al, 1996;Hymus et al, 1999). However, there is some evidence that growth in elevated pCO 2 decreases antioxidant activity (Polle et al, 1997), suggesting a possible change in potential electron flux to a Mehler reaction.…”
mentioning
confidence: 99%
“…Declines in Φ PSII, with little or no alteration in Fv' / Fm', indicates that these changes were largely associated with variations in the proportion of open PSII reaction centres (q p , or photochemical efficiency), rather than a decline in the photochemical efficiency of open reaction centres under steady state, light adapted, conditions (Fv' / Fm'), as Φ PSII = Fv' / Fm'⋅q p [15]. A similar conclusion has been suggested for changes in Φ PSII associated with the effects of low temperature, CO 2 enrichment or restricted "sink" activity [19,22]. This suggests that changes in field performance are linked to processes downstream of PSII that increasingly constrain light-driven electron flow.…”
Section: Discussionmentioning
confidence: 56%
“…One increasingly used method for assessing the "integrity" of a trees photosynthetic apparatus is via the use of chlorophyll fluorescence signals [40,41]. Although chlorophyll fluorescence assessments originally focused on measurements made on initially dark-adapted samples, there is now increasing evidence that these may not always give an accurate assessment of a plants actual photosynthetic status (under constant illuminated conditions), due to differences between light-and dark-adapted quenching processes [22]. The development of portable, pulse-modulated instruments (e.g.…”
Section: Introductionmentioning
confidence: 99%